2010
DOI: 10.1152/ajprenal.00371.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear angiotensin-(1–7) receptor is functionally coupled to the formation of nitric oxide

Abstract: The kidney is an important target for the actions of the renin-angiotensin system (RAS) and this tissue contains a complete local RAS that expresses the bioactive peptides angiotensin II (ANG II) and Ang-(1-7). We find both angiotensin type 1 (AT(1)R) and type 2 (AT(2)R) receptors expressed on renal nuclei that stimulate reactive oxygen species and nitric oxide (NO), respectively. Since Ang-(1-7) also exhibits actions within the kidney and the Ang-(1-7)/Mas receptor protein contains a nuclear localization sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 45 publications
11
90
0
Order By: Relevance
“…Indeed, it has been postulated that ACE2 is renoprotective due to its highly specific action to generate Ang-(1-7) from Ang II (21,38,59,61,62). In the kidney, the highest levels of ACE2 and the proposed Ang-(1-7) binding site are found in cortical proximal tubules (13,27,40,62). This is consistent with our results suggesting that ACE2-dependent Ang-(1-7) formation occurs mainly in renal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been postulated that ACE2 is renoprotective due to its highly specific action to generate Ang-(1-7) from Ang II (21,38,59,61,62). In the kidney, the highest levels of ACE2 and the proposed Ang-(1-7) binding site are found in cortical proximal tubules (13,27,40,62). This is consistent with our results suggesting that ACE2-dependent Ang-(1-7) formation occurs mainly in renal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…The data in that study also showed that the biphasic effect of ANG-(1-7) on the Na+/H+ exchanger occurred via the Mas receptor and that A779 (a Mas receptor antagonist) abolished this hormonal biphasic effect. These results are also consistent with previously described findings in the literature that indicated that the renal effects of ANG-(1-7) are dose dependent and mediated, at least in part, by the Mas receptor [193][194][195][196]. Nevertheless, in isolated rat proximal straight tubules (S3 segment), it was shown that, like ANG II, ANG-(1-7) exerts a biphasic effect through AT1 receptors: at physiological levels, ANG-(1-7) increases fluid and bicarbonate reabsorption, while at high concentrations, ANG-(1-7) decreases these parameters [183].…”
Section: Actions Of Ang-(1-7) In the Kidneysupporting
confidence: 93%
“…3F). A similar approach was taken for the AT 7 /Mas receptor in isolated nuclei of the sheep kidney (55)(56)(57)(58). An alomone antibody (Alomone Labs, Tel Aviv, Israel) revealed Mas receptor expression along the tubular elements of the kidney that was abolished by antibody preabsorption with the immunogenic peptide; a single band (ϳ35 kDa) was evident on the full-length immunoblot of isolated nuclei (Fig.…”
Section: Ras Protein Componentsmentioning
confidence: 97%